(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The dairy sector has adopted hazard analysis of critical control points (HACCP) systems to ensure the food safety of dairy products. Through a chain management strategy, this allows for quality verification of final goods (European Commission, 2004b). Raw milk’s quality and safety are critical for milk and the dairy products’ safety and quality. Milk contamination with bacteria, chemical residues, and other pollutants affects the safety and quality of the products. Microbial contamination is the subject of this chapter. Salmonella spp, Listeria monocytogenes and Campylobacter jejuni are examples of human microbial pathogens discovered in raw milk. A very high microbiological quality of raw milk is essential for preventing process losses and achieving an optimum shelf life for dairy products, in addition to its importance for the public health. For example, faults in semi-hard cheeses are caused by the spore formers of butyric acid bacteria in the raw milk, and raw milk contamination with Bacillus cereus bacteria reduces the shelf life of pasteurized dairy products. Quality assurance methods for dairy farms are being created, and bacteriological structures are being used in farms bulk of raw milk payment systems, in order to guarantee that bulk tank milk has a high microbiological quality. Furthermore, dairy producers’ sanitary milk production is critical for animal’s welfare and dairy industry’s image. Infections of pathogenic microorganisms affect cows (e.g., udder tissue, gastrointestinal tract), resulting in lower milk production and even mortality. In conclusion, all components of the dairy production chain benefit from the management of the microbial ecology at the dairy farm, which leads to on-farm hygienic milk productions.